SASP regulation by noncoding RNA. (December 2017) - Panda, Amaresh C.; Abdelmohsen, Kotb; Gorospe, Myriam
Abstract: Noncoding RNAs (ncRNAs), including micro (mi)RNAs, long noncoding (lnc)RNAs, and circular (circ)RNAs, control specific gene expression programs by regulating transcriptional, post-transcriptional, and post-translational processes. Through their broad influence on protein expression and function, ncRNAs have been implicated in virtually all cellular processes such as proliferation, senescence, quiescence, differentiation, apoptosis, and the stress and immune responses. Senescence is a cellular phenotype associated with the physiologic decline of aging and with age-related pathologies. Besides their characteristic terminal growth arrest and differential gene expression programs, senescent cells are known to secrete potent pro-inflammatory, angiogenic, and tissue-remodeling factors. This important trait, known as the senescence-associated secretory phenotype (SASP), influences many biological processes such as tissue repair and regeneration, tumorigenesis, and the aging-associated pro-inflammatory state. Here, we review the microRNAs, lncRNAs, and circRNAs that influence the production of SASP factors and discuss the rising interest in SASP-regulatory ncRNAs as diagnostic and therapeutic targets.